2x-1-.5-6x-x=

Simple and best practice solution for 2x-1-.5-6x-x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-1-.5-6x-x= equation:


Simplifying
2x + -1 + -0.5 + -6x + -1x = 0

Reorder the terms:
-1 + -0.5 + 2x + -6x + -1x = 0

Combine like terms: -1 + -0.5 = -1.5
-1.5 + 2x + -6x + -1x = 0

Combine like terms: 2x + -6x = -4x
-1.5 + -4x + -1x = 0

Combine like terms: -4x + -1x = -5x
-1.5 + -5x = 0

Solving
-1.5 + -5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1.5' to each side of the equation.
-1.5 + 1.5 + -5x = 0 + 1.5

Combine like terms: -1.5 + 1.5 = 0.0
0.0 + -5x = 0 + 1.5
-5x = 0 + 1.5

Combine like terms: 0 + 1.5 = 1.5
-5x = 1.5

Divide each side by '-5'.
x = -0.3

Simplifying
x = -0.3

See similar equations:

| x+(x*0.07)=131.8 | | 8/3x+1/3x=5x+65/3+7/3x | | -2(3s-1)-2=-2(5s+6)-2 | | x+8=38 | | -20x+5(2-3x)=40-6x | | 8+4(x-3)=9-5(x-4) | | x+(x*0.07)=148.35 | | 45-(2c+4)=4(c+5)+c | | 4/7+6/11 | | 6y=15 | | X+x^2+2x^2-3x= | | x+(x*0.07)=81.2 | | 6-94x=7x-9x+2 | | 15r+14=90 | | x^3-3x^2-3x+4=0 | | -k-2n-5+8n=65 | | -x+3=3x-6 | | x+(x*0.07)=63.55 | | (x+yi)(3-2i)=x(x-4i)+iy^2 | | 1x-8=2 | | x+(x*0.07)=88.30 | | h/3-5=2 | | 4x+4(80+x)=2320 | | x+(x*0.07)=52.95 | | xy+7y=2 | | -5a-3a+3b= | | -11k+14=36 | | |y-10|+8=4 | | 45=3x+6 | | 3x+-4y=9 | | 3x+6-4x-(x-8)=4(x+10) | | x^2-6x=46 |

Equations solver categories